Hydrogen-Borrowing Amination of Secondary Alcohols Promoted by a (Cyclopentadienone)iron Complex - Bai, Xishan; Aiolfi, Francesco; Cettolin, Mattia; Piarulli, Umberto; Dal Corso, Alberto; Pignataro, Luca; Gennari, Cesare (Synthesis, 2019)
Thanks to a highly active catalyst, the scope of the (cyclopentadienone)iron complex-promoted ‘hydrogen-borrowing’ (HB) amination has been expanded to secondary alcohols, which had previously been reported to react only in the presence of large amounts of co-catalysts. A range of cyclic and acyclic secondary alcohols were reacted with aromatic and aliphatic amines giving fair to excellent yields of the substitution products. The catalyst was also able to promote the cyclization of diols bearing a secondary alcohol group with primary amines to generate saturated N-heterocycles.
Keywords: hydrogen borrowing; iron; amination; alcohols; (cyclopentadienone)iron complexes